(untitled) (Journal of Medical & Health Sciences Review, 2025)
In wheat, waterlogging has a major impact on production parameters and yield. The purpose of this study was to evaluate the effects of waterlogging on wheat yield components, proline and protein content, and levels of chlorophyll b and a. Waterlogging can be caused by severe precipitation, flooding, or field drainage of a crop. Flooding occurrences are expected to become more frequent, intense, and unpredictable as a result of climate change. Each year, 10–15 million acres of wheat are impacted by this stress, which causes a 20–50% reduction in production. Given that this crop provides almost 20% of the world’s daily needs for calories and protein, it is critical to comprehend how soil & plant physiological processes differ under settings with plenty of water. This will help to significantly support population food demands. We’ll discuss how changes in wet soil’s the pH level, redox potential, conductivity of electricity, and nutrient availability impact plants’ primary responses, including root structure and growth. Waterlogging, grain for each spikes, sing-spike production, whole biomass of plants, post a thesis biomass, the leaf area at maturity were all more affected by the cultivar release year; spike for each 2 meter, 1000-grain weight, and harvest index were not significantly affected by cultivar release year. Together with the total value of photosynthetic in the top leaf, the yield of kernels and individual spikes demonstrated a significant and positive association via the leaf area at the ripening stage.